EPIDEMIOLOGY AND ETIOLOGICAL FACTORS OF ERECTILE DYSFUNCTION IN PATIENTS ON DIALYSIS AND AFTER RENAL TRANSPLANTATION - E. A. Efremov; R. R. Bekov; A. A. Dudareva; S. S. Krasnyak; D. V. Perlin (Вестник трансплантологии и искусственных органов)
Today the problem of better life quality of patients with end stage renal disease and after renal transplantation and their sexual adaptation is considered to be more impotent. The clinical part of the investigation is the obser- vation of 205 patients – men with terminal stage renal disease. Erectile dysfunction is represented in 91,4% (64) of patients getting haemodialysis, 92,3% (24) of patients getting peritoneal dialysis, 61,5% (67) of patients after renal transplantation. According to International Index of Erectile Function the mean score of erectile function is 16,7 ± 5,2 in haemodialysis patients, 19,46 ± 3,6 in peritoneal dialysis patients, 21,9 ± 5,6 in patients after renal transplantation. The analysis revealed great prevalence of erectile dysfunction and interest in improvement among the patients with end stage renal disease and after renal transplantation.